Biology of Hepatitis G Virus: A Review - Nasidi,F. A. and Rogo, L. D.* (Sokoto Journal of Medical Laboratory Science)
Hepatitis G virus (HGV) was discovered in the study of cases of hepatitis non-A, non-B, non-E. It is a linear, icosahedral, monopartite, enveloped, single stranded positive sense (ssRNA) virus belonging to the Flaviviridae family, a member of the Pegivirus genus and Hepatitis G virus (HGV) type specie. It is a blood-borne infectious pathogen without ethnic, socioeconomic, gender, age or geographic boundaries. Approximately, 750 million people are actively infected (viraemic) and an estimated 0.75–1.5 billion people have evidence of prior HGV infection. HGV RNA is detected in patients with acute (35%) and chronic (39%) hepatitis of unknown etiology. HGV RNA is also found in some patients with acute or chronic hepatitis, fulminant hepatitis patients, and chronic hepatitis C patients (21%), intravenous drug users (33%), patients on hemodialysis (3-56%), multiple blood transfused patients (58%) and hemophiliacs (18%). Several but not all studies have suggested that co-infection with HGV slows the progression of HIV disease. The mechanism responsible for the development of HGV-induced hepatitis is not clear so far. The pattern of its genetic evolution, strange properties and functional profile, its complicated connection with the host are all subjects that are far from a complete comprehension. The aim of this review was to present the current view in the biology and clinical significance of Hepatitis G virus which may be beneficial for future studies.